ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KUBIS DI DESA CIMENYAN, KABUPATEN BANDUNG - Faroby Falatehan; Ade Suryani Rifqie (Departemen Agribisnis, FEM-IPB, 2008)
Bandung Regency, Jawa Barat Province. It is one of the main producing areas of cabbage in West Java. The study used dummy variable to distinguish between planting time in the early and mid-rainy seasons. Results of analysis showed that the cabbage farms are in increasing return to scale. The regression coefficients of seeds, organic fertilizers, chemical fertilizers, pesticides and dummy of planting implied the positive significant influences on the value of output. Meanwhile, the regression coefficients of land area and pest showed the negative significant influences. Based on the dummy analysis, planting at the beginning of the rainy season is more profitable than planting in the middle of the rainy season.